A date with destiny ? - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1999)
The date has long been an important staple food in oases, and is often the main cash crop both in countries on the traditional desert trading routes of the Middle East and North Africa and in the palm groves of nomads in the Sahel and eastern...